Konsep Penanganan Masalahan Pengelolaan Sampah/Limbah Rumah Tangga di Pemukiman Kosgoro Kota Tanjungpinang - Meilisya salsabila; Amisha Auralia Putri; Alina Nisviani (Fakultas Teknik Universitas Cenderawasih, 2024)
The problem of household waste/waste is no stranger to Indonesian society. This happens because of the lack of socialization in the community about how important it is to keep the environment clean. The Kogoro Settlement, Tanjungpinang City, is one of the areas experiencing household garbage/waste problems, which until now have not found a clear solution to this problem. Residential areas, which are almost entirely above sea level, exacerbate the situation in the area due to the large amount of garbage and waste carried by sea water. This problem must be resolved as soon as possible to maintain sustainability and the ecosystem runs smoothly. Therefore the government of Tanjungpinang City issued Regional Regulation No. 03 of 2015 concerning waste management, which aims to solve various problems and provide the concept of handling management as well as sanctions for those who violate these rules. In this study, we will examine the policies implemented by the Tanjungpinang City government in dealing with environmental problems. Using the Normative-Empirical method, this research will delve deeper into these environmental problems which include the existence of sanctions, ideas, rules in Tanjungpinang including the Kosgoro settlement. However, in implementing these rules, the Government of Kosgoro did not implement them as they should. This is supported by the people who are only given advice to throw garbage into trash cans which are quite far above the settlement due to the narrow access road in the Kosgoro area. Lack of government attention makes people less aware of managing household waste and waste.